Feasibility, Benefits, and Limitations of a Penicillin Allergy Skin Testing Service. (June 2017) - Narayanan, Prasanna P.; Jeffres, Meghan N.
Objective: To critically examine the feasibility, benefits, and limitations of an inpatient penicillin skin testing service and how pharmacists can be utilized.Data Sources: A PubMed search was performed from July 2016 through September 2016 using the following search terms: penicillin skin testing, penicillin allergy, β-lactam allergy. Additional references were identified from a review of literature citations.Study Selection and Data Extraction: All English-language studies assessing the use of penicillin skin testing as well as management and clinical outcomes of patients with a β-lactam allergy were evaluated.Data Synthesis: The prevalence of people self-identifying as penicillin allergic ranges from 10% to 20% in the United States. Being improperly labeled as penicillin allergic is associated with higher health care costs, worse clinical outcomes, and an increased prevalence of multidrug-resistant infections. Penicillin skin testing can be a tool used to clarify penicillin allergies and has been demonstrated to be a successful addition to antimicrobial stewardship programs in multiple health care settings. Prior to implementing a penicillin skin testing service, institutions will need to perform a feasibility analysis of who will supply labor and accept the financial burden as well as identify if the positive benefits of a penicillin skin testing service overcome the limitations of this diagnostic test.Conclusion: We conclude that institutions with high percentages of patients receiving non–β-lactams because of penicillin allergy labels would likely benefit the most from a penicillin skin testing service.